Special aspects of the microstructure evolution at the temperature-speed deformation of a medical purpose magnesium alloy of the Mg–Zn–Y alloying system - Kristina K. Kudasheva; Mikhail L. Linderov; Aleksandr I. Brilevskiy; Aleksey V. Danyuk; Igor S. Yasnikov; Dmitry L. Merson (Frontier Materials & Technologies, 2024)
Biocompatibility makes magnesium alloys attractive functional materials in terms of their use as biodegradable implants. However, the technologies for manufacturing semi-finished products carry a possible diversity of the local strain rate and temperature within a rather wide range, which affects the processed material structure and properties. The purpose of this study is to determine the range of temperatures and resistance to deformation, at which there is no negative effect on the main structural characteristics of the processed material, using the example of a medical purposes alloy of the Mg–Zn–Y alloying system. The authors carried out mechanical tests of a biodegradable Mg–1Zn–2.9Y magnesium alloy at various temperatures and strain rates. The influence of temperatures in the range of 20...400 °C on the structure and properties of the Mg–Zn–Y system alloy is disclosed. Starting from a temperature of 350 °C, the process of dynamic recrystallisation is accompanied both by the complete restoration (return) of the original microstructure and by coarsening of the grain size, which can adversely affect the material functional characteristics. The high thermal stability of the biodegradable Mg–1Zn–2.9Y magnesium alloy is revealed, which probably results from the presence of the LPSO phase in it. The study shows that the deformation process is accompanied by twinning. At a strain rate of 2∙10−2 s−1 over the entire temperature range, the grain size distribution slightly narrows and shifts towards smaller diameters. The application of the obtained results in technological processes for manufacturing medical semi-finished products will help to solve the issue of microstructure instability at the stage of transition from a semi-finished product to a finished product during subsequent thermomechanical treatments.